The Influence of Customer Relationship Management on Customer Brand Loyalty Through Customer Satisfaction as a Mediator - Rifky Rezky Pratama; Nurafni Rubiyanti (SAFE-Network, 2023)
KRB.ID, a business specializing in selling knitted pashmina shawls for Muslim brides during engagement and wedding ceremonies. Originally operating offline at Thamrin City, Jakarta, the business faced significant changes due to the COVID-19 pandemic. With the implementation of social restrictions, KRB.ID shifted its sales strategy to an online platform, primarily utilizing Shopee marketplace. Although the pandemic limited the number of weddings, KRB.ID managed to maintain a steady level of sales. The business received positive ratings on Shopee, with an average rating of 4.9, attributed to the high-quality products that satisfied customers. However, customer service was a concern, as there were instances of delayed or incorrect responses, such as failure to confirm out-of-stock items or incorrect deliveries. The sales of knitted pashmina shawls have experienced an increase following the easing of wedding restrictions, in alignment with the evolving wedding regulations.